Green plants : their origin and diversity - Bell, Peter R. (Peter Robert), 1920-2009.; Hemsley, Alan R. (Cambridge, UK ; New York : Cambridge University Press, 2000)
"The central theme of Green Plants is the astonishing diversity of forms found in the plant kingdom, from the simplicity of prokaryotic algae to the myriad complexities of flowering plants. To help the reader appreciate this remarkable diversity, the book is arranged according to generally accepted classification schemes, beginning with algae (both prokaryotic and eukaryotic) and moving through liverworts, hornworts, mosses, fern allies, ferns and gymnosperms to flowering plants. Copiously illustrated throughout with clear line diagrams and instructive photographs, Green Plants provides a concise account of all algae and land plants, with information on topics from cellular structure to life cycles and reproduction. The authors maintain a refreshingly cautious and objective approach in discussions of possible phylogenetic relationships. Newly emerging information on features of plants known only as fossils is included, providing as complete a history as possible of the plant kingdom. Throughout the book there are many references to ultrastructural and physiological features which relate growth and form to current concepts in the study of plant development. This new edition has been completely updated to reflect current views on the origin of the major groups of plants and includes information arising from more recently developed techniques such as cladistic analyses. As such, it provides an up-to-date and timely resource for students of botany, and also for researchers needing a comprehensive reference to the plant kingdom."--Jacket
Preface -- General features of the plant kingdom -- The subkingdom algae -- part 1. The subkingdom algae -- part 2. The subkingdom algae -- part 3. The subkingdom embrophyta -- bryophyta -- The subkingdom embrophyta -- Tracheophyta, part 1. The subkingdom embrophyta -- Tracheophyta, part 2. The subkingdom embrophyta -- Tracheophyta, part 3. The subkingdom embrophyta -- Tracheophyta, part 4 -- Glossary -- Suggestions for further reading -- Index.
Includes bibliographical references (pages 327-329).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Botany; Plants -- Classification; Plants -- Evolution; Plants -- Variation; Botany; Plantes -- Classification; Plantes -- Évolution.; Botanique; Variation (Botanique); botany; SCIENCE -- Life Sciences -- Botany; Botany; Plants; Plants -- Evolution; Plants -- Variation; Plants -- Phylogeny; Plantes; Plantes -- Évolution.; Botanique; Variation (Botanique); Botany; Plants; Plants -- Evolution; Plants -- Variation; Pflanzenanatomie; Systematik; Pflanzen; Evolution; Planten; Evolutie; Phylogenèse.; Botanique; Plantes -- Classification; Plantes -- Évolution.; Plantes -- Variabilité.; evolution -- variation; Classification